2017
DOI: 10.3389/fncel.2017.00358
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miR-330-3p/PKC-α Signaling Pathway in Low-Dose Endothelial-Monocyte Activating Polypeptide-II Increasing the Permeability of Blood-Tumor Barrier

Abstract: This study was performed to determine whether EMAP II increases the permeability of the blood-tumor barrier (BTB) by affecting the expression of miR-330-3p as well as its possible mechanisms. We determined the over-expression of miR-330-3p in glioma microvascular endothelial cells (GECs) by Real-time PCR. Endothelial monocyte-activating polypeptide-II (EMAP-II) significantly decreased the expression of miR-330-3p in GECs. Pre-miR-330-3p markedly decreased the permeability of BTB and increased the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Therefore, the aberrant expression of CREBBP may have impact on calcification which is consistent with the results of the present study. Furthermore, it was reported that the translocation of CiTED1 is enhanced by the protein kinase C activator (27,28). a number of studies have set out to determine the role of mir-330-3p in different types of tumors, most of which have reported mir-330-3p-3p as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the aberrant expression of CREBBP may have impact on calcification which is consistent with the results of the present study. Furthermore, it was reported that the translocation of CiTED1 is enhanced by the protein kinase C activator (27,28). a number of studies have set out to determine the role of mir-330-3p in different types of tumors, most of which have reported mir-330-3p-3p as a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-330-3p plays a critical role in glioma, as well as in breast ( 29 ), liver, esophageal ( 30 ), lung, gastric, colon and prostate cancers ( 31 – 35 ). Although its role in cardiovascular calcification remains unclear, Liu et al ( 28 ) has proposed that miR-330-3p directs the proliferation of several types of cells, and demonstrated its negative influence of protein kinase C on the endothelial monocyte-activating polypeptide-II in the immortalized human brain endothelial cell line, hCMEC/D3. These findings indicate that miR-330-3p may be involved in the process of calcification in cardiovascular system, which was consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The blood–tumor barrier (BTB) locating between brain tumor cells and microvessels can severely block the entry of macromolecules from the blood into tumors, resulting in poor prognosis and low efficacy of glioma 2 , 3 . Although the growth of glioma can cause BTB partly damage, making it slightly more permeable than the blood–brain barrier (BBB), BTB is still a major obstacle to the delivery of anticancer drugs into the tumor 4 . Therefore, selective opening of BTB is the basis and prerequisite for the treatment of glioma 2 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a group of non-coding RNAs of about 22 nucleotides, which usually bind to the 3′ untranslated region (UTR) of mRNA, and negatively regulate expression of target genes at the post-transcriptional level. MiRNAs play important roles in biological function and are also involved in the regulation of BTB permeability 19,20 . Previous literature showed that miR-577 was downregulated in various types of tumors, including glioblastoma, hepatocellular carcinoma, colorectal cancer, et al 2124 .…”
Section: Introductionmentioning
confidence: 99%